(untitled) (Research, Society and Development, 2025)
In this paper, we aim to investigate factors such as shell adhesion, tackiness, flammability, solids content, shear strength and film formation, which are very necessary in formulation design. The core-shell microcapsules flame retardant is an important additive for increasing fire safety. Moreover, demands of free halogen flame retardants have been increasing to prevent the generation of toxic and corrosive gases during its thermal decomposition. In this research, was produced and evaluated an adhesives emulsion flame retardant free halogen based. Emulsion adhesives were applied onto a fabric flame retardant backing, adhesion increased with the time of emulsion polymerization and showed a slight decrease with increasing acrylic acid (AA). Addition of microcapsule ammonium polyphosphate with glycidyl methacrylate (MCAPP) reduced flame propagation in relation to the pure adhesive. Compounds with 25% of MCAPP showed a reduction in burn rate between 49% and 54%, and, with 10% of MCAPP decreased between 0% and 35% when compared with the pure adhesive. Microencapsulation process of the flame-retardant ammonium polyphosphate is viable and compatible with its interaction with a self-adhesive emulsion polymer and provide flame retardant characteristics to the self-adhesive, in addition to providing benefits such as being free halogen compound, increasing the thermal stability and using a water-based adhesive.